Anatomical variations of the superficial branch of the radial nerve and the dorsal branch of the ulnar nerve: A detailed electrophysiological study. Issue 6 (18th March 2021) - Hemmi, Shoji; Kurokawa, Katsumi; Nagai, Taiji; Okamoto, Toshio; Asano, Akio; Murakami, Tatsufumi; Mihara, Masahito; Sunada, Yoshihide
Abstract: Introduction: In this study we evaluated anatomic variations of the superficial branch of the radial nerve (SBRN) and the dorsal branch of the ulnar nerve (DBUN) electrophysiologically. Methods: Antidromic nerve conduction studies (NCS) of the SBRN and DBUN were performed on healthy individuals. To identify individual responses from the distal branches of the SBRN and DBUN, sensory nerve action potentials of each finger (lateral side/medial side) were recorded. Results: NCS were performed in 50 hands of 27 healthy control subjects. The thumb and the index finger were supplied by the SBRN in all cases. The lateral and medial sides of the third finger were supplied by the SBRN in 94.0% and 74.0% of the cases, but the lateral and medial sides of the fourth finger were supplied by the SBRN in only 10.0% and 2.0% of cases. The fifth finger and the medial side of the fourth finger were always supplied by the DBUN. The lateral side of the fourth finger was supplied by the DBUN in 98.0% of cases, but the lateral and medial sides of the third finger were supplied by the DBUN in 40.0% and 70.0% of cases. Dual innervation by the SBRN and DBUN was found in 34.0% and 46.0% of the lateral and medial sides of the third finger, but in only 8.0% and 2.0% of the lateral and medial sides of the fourth finger. Discussion: There are considerable anatomic variations of the SBRN and DBUN in healthy individuals.